2022
DOI: 10.1111/jan.15388
|View full text |Cite
|
Sign up to set email alerts
|

Nurse preceptors' orientation competence and associated factors—A cross‐sectional study

Abstract: Aims:To identify distinct orientation competence profiles amongst nurse preceptors and explain the associated factors. Design:A cross-sectional study design. Methods:The data were collected during the winter of 2020-2021 from registered nurses (N = 8279, n = 844) at one university hospital in Finland through an online questionnaire that included a self-administered electronic version of the Preceptors' Orientation Competence Instrument. K-means clustering was then used to identify nurse preceptor profiles. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…A number of previous studies have suggested that systematic educational interventions which enabled experienced nurses to teach, coach and mentor newer nurses facilitate the transfer of competence from experts to novices (e.g. Pohjamies et al, 2022. ) In this study, nurse leaders highlighted the importance of initiative.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have suggested that systematic educational interventions which enabled experienced nurses to teach, coach and mentor newer nurses facilitate the transfer of competence from experts to novices (e.g. Pohjamies et al, 2022. ) In this study, nurse leaders highlighted the importance of initiative.…”
Section: Discussionmentioning
confidence: 99%
“…Providing orientation for CALD nurses requires cultural orientation competence from nurse preceptors since culturally competent preceptors can enhance CALD nurses' integration into local healthcare settings (Pung & Goh, 2017). Cultural orientation competence refers nurse preceptor's ability to improve newly hired nurses' professional learning and development in a process that includes different educational steps based on the preceptees' individual needs (Peltokoski et al, 2015; Pohjamies, Haapa, et al, 2022) in a CALD environment.…”
Section: Introductionmentioning
confidence: 99%
“…The terms ‘mentor’ and ‘preceptor’ are often used interchangeably to describe experienced nurses who provide guidance and support to nursing students or newly hired nurses in a clinical setting (Chen & Lou, 2014; Pohjamies, Haapa, et al, 2022: Riden et al, 2014). However, preceptors primarily provide new employees with a short‐term orientation about workplace rules, responsibilities and clinical situations (Ke et al, 2017; Nielsen et al, 2017; Pohjamies, Haapa, et al, 2022), while mentors assist newly hired nurses to assimilate into the work environment and professional role through a deeper and longer relationship (Chen & Lou, 2014). Based on the aforementioned description, a nurse preceptor should demonstrate a high level of competence (Bartlett et al, 2020; Pohjamies, Haapa, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations